Texts : ontological status, identity, author, audience - Gracia, Jorge J. E. (SUNY series in philosophy., 1996)
"This book completes the theory of textuality whose logical and epistemological dimensions were presented in Gracia's book, A Theory of Textuality: The Logic and Epistemology (SUNY Press). It provides an ontological characterization of texts consistent with the conception of texts defended in the earlier book; it explores the issues raised by the identity of various texts; and it presents a view of the identity and function of authors and audiences and of their relations to texts. The discussion is systematic, comprehensive, and detailed. Gracia raises all of the important issues related to texts within the areas he explores and takes into account the pertinent literature. The style is argumentative and clear, and the position Gracia defends is based on common sense. He stays clear of the extreme views some contemporary authors have taken with respect to texts and textuality." "This is the only book of its kind. It is the first to develop a comprehensive theory and to adopt an integrative approach where the issues and their solutions are seen as closely connected."--Jacket